2008
DOI: 10.1097/sla.0b013e31816ffab6xxx
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Acute Phase Small-for-Size Graft Injury on Tumor Growth and Invasiveness After Liver Transplantation

Abstract: Significant activation of cell signaling pathways leading to tumor invasion and migration in small-for-size liver grafts promotes tumor growth and metastasis after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…It has been demonstrated that the cellular and molecular changes following hepatectomy, including surgical stress responses, ischemia reperfusion injury can alter the kinetics of tumor growth and thereby contribute to recurrence [16,[62][63][64] . The factors related to the surgical stress itself represent transient changes, whereas the process of liver regeneration can act as a stronger and more sustained stimulus that promotes the growth of occult tumors and neoplastic development.…”
Section: Regeneration Factors Influencing Tumor Growth and Metastasismentioning
confidence: 99%
“…It has been demonstrated that the cellular and molecular changes following hepatectomy, including surgical stress responses, ischemia reperfusion injury can alter the kinetics of tumor growth and thereby contribute to recurrence [16,[62][63][64] . The factors related to the surgical stress itself represent transient changes, whereas the process of liver regeneration can act as a stronger and more sustained stimulus that promotes the growth of occult tumors and neoplastic development.…”
Section: Regeneration Factors Influencing Tumor Growth and Metastasismentioning
confidence: 99%
“…Initiation and progression of tumor growth in the liver is a multifactorial molecular process that involves complex signaling pathways (RAS/RAF-MAPK, phosphatidylinositol-3 kinase (PI3K)/AKT, WNT/b-catenin, insulin-like growth factor (IGF), hepatocyte growth factor (HGF)/c-MET and the growth factors activating angiogenesis pathways) [12]. It has been found that cellular and molecular changes in the postoperative period of the patients who have undergone liver resection (response to surgical stress, damage due to ischemia-reperfusion) can initiate tumor growth kinetics and thus cause rapid progression [13]. The molecular factors, which are produced in the liver tissue because of surgical stress, can be a powerful stimulus for tumor growth.…”
Section: Signaling Pathways Of Regeneration and Their Impact On The Gmentioning
confidence: 99%
“…reported that significant activation of cell signaling pathways caused by this graft injury leads to cell adhesion, angiogenesis, cell invasion, and migration, which promoted tumor growth and metastasis after LT in an animal study (38). Rapid liver regeneration after small-for-size LDLT could also provide a more favorable environment for tumor growth and metastasis, as Shi et al reported, since HCC tumors developing after hepatectomy display growth rates and malignant transformations related to the size of the partial hepatectomy (39).…”
Section: Hypertension Man Et Almentioning
confidence: 99%
“…The inferior results of LDLT have been attributed to growth factors and cytokines released during acute graft injury, and subsequent graft regeneration resulting from the small-for-size graft in LDLT (36)(37)(38)(39) OS, overall survival; RFS, recurrent-free survival; RR, recurrence rate; A2ALL, Adult-to-Adult Living Donor Liver transplantation Cohort Study; N.S., not significant.…”
Section: Hypothesized Mechanism Of Increased Risk Of Recurrence With mentioning
confidence: 99%